Calculating the water surface area - a comparative analysis between results obtained from open data of optical and radar sensors - N. Mitev; S. Katsarska-Filipova; D. Filipov; P. Raeva (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Deforestation of large areas and climate change are potential flood threats. This necessitates the creation of an effective technological scheme for monitoring water bodies. The aim of this study is to analyse the results obtained from the application of open satellite data. The research team worked with radar and optical data from the Sentinel-1 and Sentinel-2 missions. The study was conducted over the period from January 2021 to December 2023. The research is focused of Koprinka dam near Stara Zagora in Bulgaria, where significant changes in the area of the water surface are observed, underlining the need for enhanced monitoring. A comparison was made between the results of optical, radar, and direct geodetic measurements. The need to compare results from optical and radar imagery arises from the fact that each has its own strengths and weaknesses, with the advantages of one type of imagery compensating for the shortcomings of the other. It is therefore crucial to determine whether the results are consistent to ensure that we have a solution at all times, regardless of climatic conditions and other factors. In order to be able to extract quantitative characteristics from the images, it is necessary to convert the resulting raster data into vector data. As a result, a vector layer with a mask of the water area of the dam for the corresponding date of the image is created from the input binary image. The final results of the research are presented in the form of a web map.